Awareness of disease in Alzheimer's disease: what do patients realize about their own condition?. (3rd October 2019) - Emery Trindade, Paula Gasparini; Santos, Raquel Luiza; Lacerda, Isabel Barbeito; Johannessen, Aud; Nascimento Dourado, Marcia Cristina
Abstract: Objective: We aim to assess different objects of awareness of disease of people with Alzheimer's disease (AD) in mild and moderate stages Method: Semi-structured interviews were conducted with 34 participants with AD and qualitative analyses were used to analyze the participants' reports. Results: Cognitive impairment was the most peserved area of awareness. The participants' explanations were mainly categorized as biological/genetic and psychosocial causes. Also, awareness of social/emotional functioning and interpersonal relationships were generally well-preserved in this group. Among those who noticed some alterations in social life, there were reports of the feeling of being exposed and how some cognitive symptoms interfere with their functioning. In the emotional state domains, most of the participants reported more sadness than before the onset of dementia. Although most participants noticed a change in routine and the impact on daily life, many did not notice the need of help for general tasks. Conclusion: Our results underpin that most people with AD were able to provide their own subjective report of their experience of living with a disease. Participants' self-reports demonstrated the differences across domains, and this information may contribute to a better understanding of awareness of disease in AD.